What Is Prohibited? Non-Academic Conduct Policies in Canadian Universities - Arney, Noah Dwain (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
Student conduct in Canadian universities is generally guided using student conduct policies, which are overseen by student affairs professionals. This structure around student conduct attempts to encourage appropriate behaviour or community standards among students attending university. The concepts of “conduct” and “misconduct” used at most universities in North America are influenced substantially by the Model Student Code template. This study examines what non-academic conduct is prohibited in the policies of universities in Canada and applies the “What’s the Problem Represented to Be” method of post-structuralist policy analysis to them. As a way to question or disrupt the representation of the “problem,” this study proposes two principles along with six guidelines for developing codes of conduct. This will help student affairs professionals and university administrators develop more educative approaches to non-academic conduct policies and provide new avenues for research into non-academic conduct.